Multi-Item Production Planning—An Extension of the HMMS Rules - Bergstrom, Gary L.; Smith, Barnard E. (Management Science, 1970)
The Linear Decision Rules (LDR) proposed by Holt, Modigliani, Muth, and Simon for the production planning problem determine an optimum plan in terms of an aggregate production rate and work force level. The criteria of the LDR assume we wish to make decisions so as to minimize costs over a specified time horizon, given estimates of future aggregate demand. This paper extends the LDR to a multi-item formulation (MDR) which solves directly for the optimum sales, production, and inventory levels for individual items in future periods. To remove the restriction of specified demand, revenue curves are estimated for each item in each time period. The MDR model then seeks a solution to maximize profit for the firm over the time horizon by an application in a firm producing a line of electric motors. The results of the MDR are compared to management's proposed plan and some important differences are detected.